Survey of the major sources of waste in the health care units of a teaching hospital - Castilho, Valéria; Castro, Liliana Cristina de; Couto, Andréa Tamancoldi; Maia, Flávia de Oliveira Motta; Sasaki, Nair Yoko; Nomura, Felicía Hiromi; Lima, Antonio Fernandes Costa; Mira, Vera Lúcia; Loyolla, Paula Manzatti (Revista da Escola de Enfermagem da USP, 2011)
The objectives of this study were to survey the different types of waste, their causes and suggestions to eliminate them according to the opinion of the nursing and medical staff from the Clinical Medicine, Surgery, Pediatrics, Rooming-In, and Nursery Units; and estimate the cost of the major source of waste found in the referred units. This descriptive, explorative study was performed at the University of São Paulo Teaching Hospital using a quantitative approach. The study sample consisted of 189 medical and nursing professionals. Material waste (36%) was the most often reported by all professional categories, followed by physical structure waste (27%). The most reported wasted materials were medicines, dressing packs, stationary paper, and infusion devices The estimated annual cost of material waste in the studied units is about R$ 479.262,86.